2016
DOI: 10.1097/mcg.0000000000000434
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Utility of Evaluating the Luminal Upper Gastrointestinal Tract During Linear Endoscopic Ultrasonography

Abstract: A substantial minority of patients undergoing L-EUS for nonluminal indications will have clinically meaningful luminal findings. The endoscopic evaluation of the luminal upper GI tract can be adequately achieved using the linear echoendoscope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In this study, detection rate of gastric lesions could be increased by brief screening of the stomach. Some studies comparing EUS/ERCP and EGD showed that there was no difference in the rate of missed gastric lesions [14,15]. In contrast, Ashby et al reported that ERCP or EUS followed by EGD resulted in an approximately 20% increase in the detection rate of gastric lesions [7].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, detection rate of gastric lesions could be increased by brief screening of the stomach. Some studies comparing EUS/ERCP and EGD showed that there was no difference in the rate of missed gastric lesions [14,15]. In contrast, Ashby et al reported that ERCP or EUS followed by EGD resulted in an approximately 20% increase in the detection rate of gastric lesions [7].…”
Section: Discussionmentioning
confidence: 99%
“…In patients undergoing EUS for pancreaticobiliary or mediastinal indications, three studies found clinically relevant luminal lesions of the upper GI tract in 20.5%–29.7% of cases. [106107108] A multicentric prospective study reported that EGD performed prior to EUS found luminal lesions impacting the subsequent endosonography in 9.8% of cases. [107] Therefore, routine performance of EGD before longitudinal EUS may be worthwhile.…”
Section: Do We Need Egd Prior To Eus?mentioning
confidence: 99%
“…[109110] The miss rate of clinically relevant lesions using a longitudinal echoendoscope to evaluate the luminal surface of the upper GI tract in one prospective multicenter study was not inferior to EGD. [108] EGD always requires air insufflation. The removal of insufflated air for EUS may be time-consuming and incomplete.…”
Section: Do We Need Egd Prior To Eus?mentioning
confidence: 99%